2017
DOI: 10.3389/fpsyg.2017.01932
|View full text |Cite
|
Sign up to set email alerts
|

Audio Spatial Representation Around the Body

Abstract: Studies have found that portions of space around our body are differently coded by our brain. Numerous works have investigated visual and auditory spatial representation, focusing mostly on the spatial representation of stimuli presented at head level, especially in the frontal space. Only few studies have investigated spatial representation around the entire body and its relationship with motor activity. Moreover, it is still not clear whether the space surrounding us is represented as a unitary dimension or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Most importantly, while the size of PPS representation around the trunk is relatively constant, PPS representation around the hand or the face vary according to their position relative to the rest of the body and relative to the trajectory of the stimulus relative to the body ( Figure 4B ). These observations are confirmed by more recent studies ( Aggius-Vella et al, 2017 ) and also generalize to lower body segments ( Stone et al, 2017 ). Indeed, Stone et al observed that participants have speeded RTs to a tactile stimulus applied to the feet when a visual stimulus approaching the legs.…”
Section: Different Representations Of Body-related Ppssupporting
confidence: 88%
“…Most importantly, while the size of PPS representation around the trunk is relatively constant, PPS representation around the hand or the face vary according to their position relative to the rest of the body and relative to the trajectory of the stimulus relative to the body ( Figure 4B ). These observations are confirmed by more recent studies ( Aggius-Vella et al, 2017 ) and also generalize to lower body segments ( Stone et al, 2017 ). Indeed, Stone et al observed that participants have speeded RTs to a tactile stimulus applied to the feet when a visual stimulus approaching the legs.…”
Section: Different Representations Of Body-related Ppssupporting
confidence: 88%
“…In the lower space actions are mediated by foot, and during ambulation, audio and motor feedback are linked. The representation of auditory frontal space around the chest is more accurate than the auditory frontal representation around the foot 27 . Therefore, forward leaning of the trunk seems to be a strategy related to maximizing the quality of auditory inputs to guide postural control during passing/receiving the ball.…”
Section: Discussionmentioning
confidence: 92%
“…Auditory-motor performance, such as reaching and pointing to auditory targets, is also influenced by the location of a sound source in relation to the listeners' heads. For instance, pointing error to auditory targets has been found to be smaller at the height of the chest than at the height of the feet 20 . Furthermore, higher accuracy of pointing to auditory targets was observed under the condition in which listeners showed a larger heading angle to the targets, as well as with a larger amplitude of head movements 21 .…”
Section: Blind Footballers Direct Their Head Towards An Approaching Bmentioning
confidence: 99%